Transformasi Energi Kampung: Teknologi Solar Panel untuk Rumah Tangga, Pertanian, Dan Kerajinan Lokal Papua Agar Meningkatkan Ekonomi Dan Industri Kreatif Masyarakat Asli Papua Kampung Duwin - Teguh Santoso; Syahira Syahira; Wiska Baharuddin; Machmud Effendy; Untung Santoso; Yus Mochamad Cholily (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This community service program aims to implement solar panel technology to support household electricity needs, local Papuan craft production, agricultural irrigation, corn processing into animal feed, and strengthening the marketing of Duwin Village community products. The activity used a pilot project approach combined with Participatory Rural Appraisal and Rapid Rural Appraisal. Participants consisted of 20 members of the craft group and 20 members of the agricultural group. Data were collected through observation, interviews, and pre-test and post-test questionnaires, then analyzed descriptively qualitatively and quantitatively. The results showed the strongest increase in the application of solar panels for household needs and craft production, with a score increase of 407 points or 92.7% and an average gain of 2.04. Social media training, product arrangement, understanding market trends, and the use of container booths increased the score by 446 points or 89.6%, with an average gain of 2.03. The implementation of solar water pumps and corn grinding machines increased the score by 349 points or 69.8%, with an average gain of 1.74.